Analysis Workshop Management, Time Management and Problem Solving Ability to Automotive Electrical Competence - Arizal, Heru; ., Suparji; ., Marniati; Suhartini, Ratna; Ramadani, Ali Hasbi; Rahayu, Imami Arum Tri (Journal of Ecohumanism, 2025)
In the 21st century, the industrial revolution 4.0 occurred where required to change aspects of human life. Therefore, the quality of human resources must also be carried out increase. The quality of human resources can be seen in terms of their competence at work. In this study, we want to identify the factors that influence competence, especially in the automotive electrical. The data analysis of this research is using SEM analysis to see the direct and indirect effect on competence. The results showed that workshop management had a significant effect on the ability to solve problems, while time management did not directly affect the ability to solve problems and competence. Partially, workshop management and problem solving ability have a significant direct influence on competence. Competence is influenced indirectly by workshop management through the ability to solve problems. In contrast to time management which does not affect competence indirectly through problem solving ability. Therefore, in order to improve student competence, it is necessary to do improvement of problem solving ability and improvement of workshop management qualityIn the 21st century, the industrial revolution 4.0 occurred where required to change aspects of human life. Therefore, the quality of human resources must also be carried out increase. The quality of human resources can be seen in terms of their competence at work. In this study, we want to identify the factors that influence competence, especially in the automotive electrical. The data analysis of this research is using SEM analysis to see the direct and indirect effect on competence. The results showed that workshop management had a significant effect on the ability to solve problems, while time management did not directly affect the ability to solve problems and competence. Partially, workshop management and problem solving ability have a significant direct influence on competence. Competence is influenced indirectly by workshop management through the ability to solve problems. In contrast to time management which does not affect competence indirectly through problem solving ability. Therefore, in order to improve student competence, it is necessary to do improvement of problem solving ability and improvement of workshop management quality.